Bone health program: A community cancer center's experience. Issue 28 (1st October 2022) - Anipindi, Manasa; Venigalla, Tejaswi; Al-Sudani, Hussein; Provenzano, Noelle; Ali, Rafal; Gilani, Madiha Atif
Abstract : 360 Background: Aromatase inhibitors (AI) are an essential treatment for postmenopausal women with hormone receptor-positive breast cancer in the adjuvant setting. Estrogen deficiency caused by AIs has adverse effects on bone health. Studies reveal that 5 years of treatment with anastrozole led to 6.1% of bone loss at the lumbar spine and 7.2% at the hip. The aim of the project is to identify the current degree of attention to bone health and skeletal-related complications in women with early-stage breast cancer stages I-III that are on AIs at a community cancer center at Einstein Medical Center Montgomery. Methods: This is a retrospective chart review of 63 patients ages 50-85 diagnosed with early-stage I-III breast cancer on an AI in the adjuvant setting. Patients who started on an AI between January 2013 through December 2017 were included. Data on Dual-energy X-ray absorptiometry scans (DEXA) and treatment at baseline, 2-years, and 4-years were analyzed. We followed to see if they had a DEXA scan every 2 years after the baseline DEXA scan for the following 4 years and analyzed information on their bone health. Results: Patients included were on an AI throughout the 4 years. The median age was 60.2 years. 46/63 (73%) had a baseline DEXA scan. Out of these, 12/63 had a normal bone density. 28/63 had osteopenia, of which 16/28 were treated. 6/63 had osteoporosis and only 2/6 were treated. After 2 years, 39/63 (61%) had a 2-year DEXA scan. Of these, 8 had a normal bone density. 26/63 had osteopenia of which 21/26 were treated. 5/63 had osteoporosis and all 5 were treated for this. At 4 years, 40/63 (63%) had baseline DEXA scans. 9/63 had a normal bone density. 21/63 had osteopenia, out of which 17/21 were treated. 10/63 had osteoporosis of which 5/10 were treated. Conclusions: Patients who are being treated with aromatase inhibitors should be evaluated for baseline bone health prior to initiating AIs and every 2 years thereafter. Treatment with bisphosphonates or RANK ligand inhibitors is recommended at an earlier T-score compared to post-menopausal osteoporosis in the absence of breast cancer. In our study, we noticed that the number of patients who did not receive a DEXA scan at the correct time points increased during the period of treatment with the AI. About 53% of patients had osteopenia or osteoporosis at the time of initiation of AIs. The amount of osteoporosis in patients increased from 9.5% at baseline to 15.8% at the 4-year point. This data indicates the need for proper guidelines on DEXA scans and interventions for this patient population. Current interventions planned are patient education Flyers, a patient risk factor checklist in the EMR (Electronic Medical Record) and prompts to review the status of the DEXA report when ordering AIs.